Income enhancement through community oriented sheep breed improvement - Avinashilingam, N A Vijay; Patel, A K; Singh, S K; Rohilla, P P; Bhojaram, Sharvan Ram (Indian Farming, 2019)
In a developing country like India, the livestock sector is considered to be one of the fastest growing agricultural subsectors with a share of about 33% in agricultural GDP. Due to the rapidly increasing demand for livestock and its byproducts, this sector is considered more lucrative than others. In livestock, small ruminants play an important role in Indian economy by providing livelihood to two-thirds of the rural community.